Entrepreneurial Activity of Institution of Higher Education: Learn From American Experience - Давидова, Наталія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Postsecondary educational institutions have expanded the scope of commercial activity that now involves the institution in the sale of goods, services, or leasehold interests in real estate. The trend toward commercialization of college and university operations continues to emerge which means the growth of commercial activities and related entrepreneurial activities. These developments may affect the institutions, their campus communities, and local communities in many ways: some good and some not so good, and may also raise questions about the academic values and institutional mission. The educational institutions may engage in such activity for a variety of reasons. The goal may be to make the campus life more convenient and self-contained, to increase institutional visibility and show good will with professional and corporate organizations, to make productive use of underutilized space, especially in the summer, to generate new revenue streams and become self-supporting. It is reasonable to learn from the positive experience of American institutions of higher education and implement it in Ukrainian system of education. The scope of an institution's authority to perform entrepreneurial activity may be questioned whether or not the institution's activity puts it in competition with local businesses. Challenges may be made by business competitors, by state taxpayers, or by the state attorney general. Early and modern legal precedents illustrate the variety of approached that courts may use in analyzing the authority of a public institution to engage in arguably commercial activities or to compete with private business enterprises. The circumstances that should be taken into account are: (1) particular functions and objectives of the enterprise, (2) the relation of these functions and objectives to the institution's educational purposes, (3) the particular wording of the statutes or constitutional provisions delegating authority to the institution or limiting its powers, (4) judicial precedent in that state indicating how to construe the scope of delegated powers. If a court finds that commercial activities serve an educational function or are related to the institution's educational purposes, it probably would conclude that the institution has the authority to operate the enterprise. In contrast, the institution's authority will likely be questionable or nonexistent if the competitive or profit-seeking aspects of its enterprise are not incidental to its educational aspect but rather are the primary driver behind the institution's decision to operate the enterprise.